Arbitraje + Tecnología = Eficiencia, ¿dónde? - Espejo Donaire, Andrea (2021)
In a globalized and ever-changing world, Arbitration is at a crossroads for its development, where the information technologies are slowly being introduced and taking a starring role. The author explores five key areas where technology plays an essential role in Arbitration, not only in the present, but also where it is headed in the near future.